PERANAN BADAN PERMUSYAWARATAN DESA DALAM PERENCANAAN PEMBANGUNAN DI DESA DOLOK MARGU KECAMATAN LINTONG NIHUTA - Sinaga, Sutinar; Manalu, Dimpos; Rajagukguk, Jonson (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
This study aims to determine the role of the Village Consultative Body in Development Planning in Dolok Margu Village, Lintong Nihuta District. The type of research used was qualitative research with data collection methods through observational studies, interviews and direct documentation at the Dolok Margu Village Office, while the informants in this study were the Village Head as key informant, Chair of the Village Consultative Body and BPD Members as the main informant, and community leaders as supporting informants. The results of the study show that the implementation of the main tasks of the Village Consultative Body in the governance of the village of Dolok Margu has not been fully carried out optimally based on the law that has been set. Constraints on the non-implementation of the functions of the Village Consultative Body due to factors, lack of knowledge such as incompetent human resources regarding the duties and functions of the Village Consultative Body (BPD) due to the very low level of human resources education, as well as land budget adjustments that have not been optimal and factors facilities that do not yet have a special office for the Village Consultative Council which causes the Village to be in the planning, implementation and supervisory stages not running effectively.